DAMPAK OBJEK WISATA PANTAI CAROCOK BAGI KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI NAGARI PAINAN SELATAN KECAMATAN IV JURAI PESISIR SELATAN - -, Finnora - (Pendidikan Geografi, 2014)
Tourisme is part of industrial sector in Indonesia that prospect bright, and have potensial withvery big calm for to develop. West sumatera is Area Direction a tourt,be source tonmo vement a fourgnttourt.One of the tourisme area region of province west sumatera has prioritas to develope of governmentarea Pesisir Selatan district Painan is Carocok Beach attraction is set as the center of tourisme with naturefacility tirta beach The observation to purpose description to crash object tourisme in the carocok beachfor social â economic life of the people in the south painan the District IV jurai Pesisir Selatan.The observation to get information, anality and to study data about to crash tourisme object thecarocok beach for social-economic life of the people in the south Painan the District IV jurai south coast.This type of research is descriptive. The study population is head of the family in the area tourisme objectin south Painan the district 1.260 KK. The sampel of respondence was determined using a proportionalsampel taken 10-15% so that the sampel respondence amounted 126 KK.Based on the anality descrition it can be concluded as follows: 1) Income before and after thedevelop Beach Carocok South Painan the District IV jurai south coast before develop Rp. 500.000-700.000 month (50%)and after develop Rp. 701. 000-900.000 (31,75%) income after develop getolevel.2) Education before and after develop Carocok Beach in the south painan district Iv jurai south wastdevelop before (36,51%) is primary scholl, while developing after (34,13%) is a graduate high school. 3)Security before and after develop carocok beach south painan district IV jurai south coast before develop(51,59%) is a middle, after develop (31,75%) is a security. 4) Social interaction before and after developcarocok beach in the south painan district IV jurai Pesisir Selatan. Develop before (53,97%) is less goodwhile develop after (50,79%) is good.